2017
DOI: 10.1007/s11096-017-0534-3
|View full text |Cite
|
Sign up to set email alerts
|

Introducing clinical pharmacy services to cardiovascular clinics at a university hospital in Northern Cyprus

Abstract: Background Clinical pharmacists are the primary source of scientifically valid information and advice on the safe, rational, and cost-effective use of medications. However, ward-based clinical pharmacy services are not well optimized in Northern Cyprus. Objective Ward based clinical pharmacy services were introduced and evaluated in cardiovascular clinics. Setting Cardiology and cardiovascular surgery departments in a tertiary university hospital. Methods A prospective interventional study introduced and docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 25 publications
5
16
1
8
Order By: Relevance
“…In our study, treatment effectiveness was the dominant type of DRPs, and this was similar to the study evaluating clinical pharmacy services to cardiovascular clinics in Northern Cyprus [18]. Patient-related category and drug selection accounted for approximately 50% causes of the DRPs in that study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, treatment effectiveness was the dominant type of DRPs, and this was similar to the study evaluating clinical pharmacy services to cardiovascular clinics in Northern Cyprus [18]. Patient-related category and drug selection accounted for approximately 50% causes of the DRPs in that study.…”
Section: Discussionsupporting
confidence: 83%
“…For example, a study in hospitalized surgical patients in China reported a mean of [17]. The study in cardiovascular units in Northern Cyprus demonstrates that 61% of patients had DRPs using the PCNE classification V6.2, and the average DRPs per patient was 1.6 [18]. Another study done in an internal medicine ward in Turkey indicates that 80% of patients had DRPs using PCNE classification V7.0, an average of 1.6 DRPs per patient [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that PI were efficient and had an acceptance rate of 98.1%. These results seem to be more important than those described in another recent publication 17 and could probably be explained by the complete involvement of the senior pharmacist in the cardiologic units. The equal distribution of interventions detected by MR and prescription analysis demonstrates the complementarity of these two activities.…”
Section: Discussionmentioning
confidence: 44%
“…The shift from traditional pharmacy practice to patient-oriented care causes more collaboration between clinical pharmacists and other healthcare providers. As a result of this collaboration, it was determined that patient care was more effective, drug-related problems decreased, and more successful outcomes were achieved in treatment [6][7][8]. Therefore, the establishment and development of pharmaceutical care is of high importance in order to increase the level of collaboration between clinical pharmacists and other healthcare providers [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Riyadh, Saudi Arabia, It has shown that physicians and nurses have positive perceptions of clinical pharmacy services, but that awareness should be raised by taking a more active role in the work environment [13].In another study conducted in Northern Sweden, it has been shown that all of the physicians who had a positive perspective, were satisfied with their collaborative work with clinical pharmacists [14]. There is an enormous change in the field of clinical pharmacy in Northern Cyprus in recent years [7,[15][16]. There have been necessary changes in pharmacy education to use the skills of the clinical pharmacist in the changing health care system [17].…”
Section: Introductionmentioning
confidence: 99%